2021
DOI: 10.1055/s-0040-1722321
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Standardized Knee Functional Assessment in Predicting the Outcomes of Total Knee Arthroplasty

Abstract: Questionnaires and physical tests are tools to determine the ability of an individual to perform tasks of the daily living. In our institution, a standardized knee performance evaluation including patient-reported outcome measures (PROMs) and physical performance tests has been applied to all patients undergoing total knee arthroplasty (TKA). Our goal was to identify which preoperative tools influence the outcomes of a TKA and if physical performance tests can be of value if used along with PROMs in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…It should be noted that 5 studies exclusively recruited women ( 52 56 ), in one study only men were included ( 51 ), one study did not provide information on the sex ( 35 ) and in 3 studies the mean age was not provided or specified ( 49 , 55 , 57 ). The youngest average age was 24.1 ( 58 ) and the oldest 80.5 ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that 5 studies exclusively recruited women ( 52 56 ), in one study only men were included ( 51 ), one study did not provide information on the sex ( 35 ) and in 3 studies the mean age was not provided or specified ( 49 , 55 , 57 ). The youngest average age was 24.1 ( 58 ) and the oldest 80.5 ( 59 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 31 included studies, 29 were observational (15 were cross-sectional ( 12 , 52 , 53 , 55 , 56 , 58 67 ), 7 retrospective ( 28 , 35 , 48 , 49 , 68 70 ), 6 prospective ( 51 , 57 , 71 74 ) and 1 combined analysis of retrospective and prospective occurrences ( 75 ) in cohort studies) and 2 were interventional [clinical trials ( 50 , 54 )]. BMI classification was monitored for all the included studies according to the WHO standards; however, not all the studies made use of a complete subclassification stratified in four classes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 , 21 , 28 ) Several studies have demonstrated that preoperative and early postoperative TUG times are useful for predicting both short- and long-term mobility function following lower-limb arthroplasty. 29 , 30 ) In patients after THA, one previous study suggested that the TUG test in the early stage was an effective indicator to predict ambulation ability at 6 months after surgery. 31 ) Poitras et al reported that the preoperative and postoperative day 2 TUG time could indicate hospital LOS and short-term functional capacity.…”
Section: Discussionmentioning
confidence: 99%